The effectiveness of different immunotherapies in the treatment of condyloma acuminatum: a network meta-analysis of randomized clinical trials - Liu, Xiaoye; Qi, Manli (Frontiers in Medicine, 2023)
Background: The treatment of condyloma acuminatum (CA), especially the very persistent and recurrent CA, is currently the focus of our research. Immunotherapies have recently been shown to be well-tolerated and effective in treating warts, particularly refractory warts. However, there is still a lack of corresponding evidence-based medical evidence on the effectiveness of different immunotherapies in treating warts. The difference between network meta-analysis and meta-analysis is that network meta-analysis can be used to compare multiple treatments by combining direct and indirect evidence to assess the interrelationship between all treatments. We intend to compare the efficacy of different treatments for CA using a network meta-analysis. Methods: PubMed, Cochrane Library and Embase from inception to June 1st, 2023 were searched using a computer. All articles on immunotherapies for CA were included. Stata MP17.0 software was used for data analyses. Results: A total of 8 randomly-controlled trials involving 493 patients were included. Result showed that all treatment measures had a significant efficacy compared with the regular saline group (BCG (bacillus Calmette-Guérin vaccine) OR=96.00, 95%CI: